Anti-CD3 antibody ameliorates experimental autoimmune uveitis by inducing both IL-10 and TGF-β dependent regulatory T cells - Ke, Yan (2011)
Chronic/recurrent autoimmune (idiopathic) uveitis is difficult to treat and they account for approximately 10% of legal blindness in the Western world. As it has been reported that anti-CD3 antibody can enhance T cell regulatory function, we investigated its effects in vivo on experimental autoimmune uveitis (EAU), a model for autoimmune uveitis in humans. B10RIII mice immunized with an uveitogenic peptide were treated with the F(ab')2 fragment of anti-CD3 mAb either before or at clinical disease onset. Evaluation of EAU and cellular responses showed that disease was inhibited and the activation and expansion of pathogenic T cells selectively reduced, whereas functions of Treg in vivo were enhanced. Moreover, mice treated with anti-CD3 mAb were resistant to a second challenge with antigen and thus protected from recurrence of disease. Our results demonstrate that anti-CD3 mAb is a potent inhibitor of autoimmune uveitis.